Mapping the research trends and hot topics of ventricular arrhythmia: A bibliometric analysis from 2001 to 2020 - Wang, Shiwei; Jia, Tianyuan; Liu, Guoxiang; Lu, Xiaoye; Yang, Qian; Zhu, Changqing (Frontiers in Cardiovascular Medicine, 2022)
Background Studies of ventricular arrhythmia (VA) have drawn much scholarly attention over the past two decades. Our study aimed to assess the current situation and detect the changing research trends of VA quantitatively and qualitatively. Materials and methods All the information used in our statistical and bibliometric analysis were collected and summarized from papers retrieved from the Web of Science Core Collection (WoSCC) database on December 22, 2021 using certain criteria. Visual analytics were realized using CiteSpace, VOSviewer, the bibliometrix R package, and the bibliometric online analysis platform. Results A total of 6,897 papers (6,711 original articles, 182 proceedings papers, three book chapters, and one data paper) were published in 796 journals that concentrated on the research areas of cardiovascular and critical care medicine. The most productive country and influential institution was the USA and the Mayo Clinic, respectively. Heart Rhythm (551 articles and 8,342 local citations) published the most manuscripts. The keyword co-occurrence and co-citation network of references analyses revealed that the most popular terms were ventricular tachycardia, ventricular fibrillation, catheter ablation, implantable cardioverter defibrillator (ICD), and sudden cardiac death (SCD). Further, the burst detection analysis demonstrated that topics strongly associated with clinical prognosis, such as meta-analysis, long-term outcomes, and impact, were new concerns. Conclusion Our study offers a comprehensive picture of VA research and provides profound insights into the current research status. Moreover, we show that new topics within the VA research field have focused more on prognosis and evidence-based clinical guidelines.